Middle-Class Consensus, Social Capital and the Mechanics of Economic Development - Stefan Dietrich Josten (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2005)
This paper analyzes a heterogeneous-agents endogenous-growth model incorporating both transaction costs and social capital. An individual can either become an active part of the society?s middle-class networks of trust and mutual cooperation, thus making a positive contribution to overall social capital. Alternatively, the individual can stay socially disintegrated and free-ride on the community?s social capital. Due to the existence of asymmetric information, agents face a moral-hazard problem on the credit market which gives rise to transaction costs and can be alleviated by private, governmental or social governance structures. An increase in inequality and shrinking of the middle class depresses the community?s social capital, which, in turn, weakens the informal social governance system and increases economy-wide transaction costs. As a result a more unequal distribution lowers the economy?s growth rate.
urn:nbn:de:gbv:705-opus-16626
Keywords: O41; D3; Z13; 330; Social Capital; Inequality; Middle Class; Economic Growth; Distribution; Entwicklung; Mittelstand; Social Capital; Neue Wachstumstheorie; Transaktionskosten; Theorie